Photo-Fenton of Dyes Degradation Using Covalent Triazine Frameworks: Toward Industrial Wastewater Treatment Applications - Prawiranegara, Barata Aditya; Sugesti, Heni; Suhendri; Abid, Hussein Rasool; Azhar, Muhammad Rizwan; Rada, Zana Hassan; Manawan, Maykel; Utama, Panca Setia (Journal of Applied Materials and Technology, 2024)
A Covalent Triazine Framework (CTF-1) and carbon nanospheres (CS) were synthesized to develop a porous, thermally stable, and efficient photocatalyst for dye degradation in wastewater treatment applications. The synthesized composite material exhibited a high surface area exceeding 400 m²/g, a well-defined mesoporous structure, and excellent optical properties, including strong light absorption extending up to 550 nm and a moderate band gap of approximately 2.8 eV. These characteristics promote effective visible light-driven photocatalysis. The photocatalytic performance was assessed by degrading methylene blue (MB) as a model organic dye pollutant under photo-Fenton conditions. The system demonstrated high efficiency, with over 90% of the dye removed within 120 minutes of irradiation. The degradation followed pseudo-first-order kinetics, confirming the photocatalytic nature of the reaction. Parameter studies indicated that hydroxyl radicals (•OH) were the dominant reactive species responsible for dye degradation. Moreover, CTF-1 retained its photocatalytic activity and structural integrity over multiple reuse cycles, showcasing excellent reusability and stability. The integration of high surface area for dye adsorption, efficient photoactivation under visible light, and robust radical generation synergistically contributed to the enhanced degradation performance. The study highlights the promising role of CTF-1 and its composites as multifunctional materials for advanced oxidation processes. Given its effectiveness, durability, and environmental compatibility, CTF-1 presents a sustainable and scalable solution for the treatment of dye-laden industrial wastewater. This work contributes to the development of next-generation photocatalysts aimed at addressing global challenges in water pollution and environmental remediation.